Zinc ion interactions in a two-dimensional covalent organic framework based aqueous zinc ion battery - Mohammed, Abdul Khayum; Ghosh, Meena; Vijayakumar, Vidyanand; Halder, Arjun; Nurhuda, Maryam; Kumar, Sushil; Addicoat, Matthew; Kurungot, Sreekumar; Banerjee, Rahul (Chemical Science, 2019)
<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">The two-dimensional structural features of covalent organic frameworks (COFs) can promote the electrochemical storage of cations like H<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, Li<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, and Na<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> through both faradaic and non-faradaic processes. However, the electrochemical storage of cations like Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ion is still unexplored although it bears a promising divalent charge. Herein, for the first time, we have utilized hydroquinone linked β-ketoenamine COF acting as a Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> anchor in an aqueous rechargeable zinc ion battery. The charge-storage mechanism comprises of an efficient reversible interlayer interaction of Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ions with the functional moieties in the adjacent layers of COF (−182.0 kcal mol<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">). Notably, due to the well-defined nanopores and structural organization, a constructed full cell, displays a discharge capacity as high as 276 mA h g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> at a current rate of 125 mA g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">.